Relationship between Genetic Variability and Land Use and Land Cover in Populations of Campomanesia adamantium (Myrtaceae) - Bruno do Amaral Crispim; Miklos Maximiliano Bajay; Adrielle Ayumi de Vasconcelos; Thamiris Gatti Deo; Ramilla dos Santos Braga; Mariana Pires de Campos Telles; Maria do Carmo Vieira; Thiago de Oliveira Carnevali; Julio César Jut Solórzano; Alexeia Barufatti Grisolia (Diversity, 2018)
Campomanesia adamantium is an endemic plant of Cerrado biome that has potential for cultivation because its fruits have culinary and medicinal uses. However, genetic diversity studies using molecular markers with Cerrado species are scarce, and the inadequate extractive exploitation of fruits and the expansion of agricultural frontiers may also affect genetic variability. Therefore, studies in this field are of interest as they can provide sources for conservation and breeding programs. In this context, we investigated the genetic diversity of native populations of C. adamantium from different sites and the relationship between genetic variability and the land use and land cover of each site. A total of 207 plants were sampled in seven sites and characterized with seven polymorphic microsatellite markers. The use and coverage of land were mapped based on aerial images, and the land was classified into different categories. The genetic diversity was high in all populations, with low levels of differentiation due to allele sharing, mainly in Mato Grosso do Sul and Paraguay populations. The geographically closest populations were more genetically similar. The use and coverage of land indicated that intense agriculture promotes a significant decrease in genetic variability.